Voluntariado educativo: uma experiência de ser com os demais - Braga, Juliana Lima dos Santos (Universidade do Vale do Rio dos Sinos, 2022)
The present work aims to analyze the possible contributions of educational volunteering that takes place at Colégio Santo Inácio/RJ, which is part of the Jesuit Education Network (RJE) in Brazil, for processes of integral formation and lifelong education, recognized by the students who participated in it and pedagogical managers, and how these could help to improve the management of the program. To this end, the path taken was based on a qualitative approach, where data collection was carried out entirely online, due to the pandemic context of social isolation (Covid19) and was composed of three stages: online questionnaire for students, synchronous online focus group and online questionnaire for College managers (sent by email). The collected data were analyzed using the thematic content analysis technique, which allowed two final categories to be found: compassion (which opens the way for solidarity) and commitment (for the promotion of justice). For students and managers, these were the aspects and effects that stood out when reflecting on educational volunteering in the perspective of integral formation and education for life. Through the research carried out, it was possible to verify the importance of educational volunteering for the process of training students for the human excellence desired in Ignatian education, illustrated by the 4 C's: being conscious, competent, compassionate and committed. Educational volunteering has shown the potential to stimulate the latter two, according to experiences shared by both students and managers. Such reports also led to an intervention proposal that further involves educational volunteering in the institution's curriculum, in addition to emphasizing the need to reach other students who do not participate. The title of this work summarizes what throughout the research stood out as one of the great training opportunities contained in educational volunteering: the experience of being with others.
Keywords: Voluntariado educativo; Compassividade; Comprometimento; Educational volunteering; Compassion; Commitment; ACCNPQ::Ciências Humanas::Educação